Inclusive education for all: Principles of a shared inclusive ethos - Kohout-Diaz, Magdalena (European Journal of Education, 2023)
This article discusses paradoxes that, in theory and in practice, hinder the deployment of inclusive education. The first type of paradox is related to the confrontation between the humanist ideals conveyed by inclusive approaches and contemporary political discourses. These difficulties are linked to (1) the very concept of inclusion; in which the universal, particular, and singular dimensions are dialectically articulated. The paradox is also linked to (2) the orientation of contemporary political discourses in Europe; notably, deinstitutionalisation, intentions to stop specialised care and support, and the deployment of standardised software to assist assessment and learning at schools. The second type of paradox confronts the situational approach to special education needs with the contemporary trend towards homogenisation of nomenclatures and reference categorisations. Extremely vague definitions of guiding concepts lead to the devaluation of pedagogical approaches. This in turn contributes to the maintenance, or even domination, of biotechnical approaches. This comes at the cost of less attention to cooperative multidisciplinary approaches which have proven their effectiveness. These paradoxes can and should be addressed both (1) at the level of the individual ethical responsibility of professionals in the field and (2) in the context of teaching and learning practices. The article formulates four principles to enable teachers, as interpreters of diversity, to move towards an ethic that does not deny the unpredictability and uncertainty inherent in the infinite variety of forms of learning and education, but which on the contrary makes it a genuine source of innovation and pedagogical creation.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/ejed.12560